WARÔNG KUPI SEBAGAI PUBLIC SPHERE DAN PENGARUHNYA TERHADAP SOCIAL MOVEMENT MASYARAKAT DI KABUPATEN ACEH BARAT - Saiful Asra; Yudhi Fahrimal (Universitas Teuku Umar, 2017)
This study aims to find out how the representation of Warong Kupi as a Public Sphere among the people of West Aceh District. Using a qualitative approach based on constructivist paradigm, this research would like to find out how the subjective meaning of representation warong kupi in aceh and its relation with social movement of society. The object of research studied in this research is coffee shop as public sphere facility itself and involving parties that have been determined by base method in writing this research. The results obtained from this research is Warong kupi ultimately became the arena of discourse various themes of conversation. The topics of Kupi warong talks became very diverse ranging from politics, social, economic, and so forth. However, the political theme dominates the discourse of warong kupi in Aceh Barat. This is due to the interest of the people of West Aceh on the political theme, although in contrast not all West Aceh people boast of their political literacy level. Keyword :: Public Sphere, Warong Kupi, Politic of Representation.